PROFESSIONAL TRAINING OF TRANSLATORS IN THE US EDUCATION SYSTEM - Катерина Скиба (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The intensive development of international relations affects the increase in cross-language communication. The role of professional translators is growing. The honourable first place among the leaders in the educational services provision is occupied by the United States of America. Differentiated network of educational institutions of the USA offers multi-level training programs for translators and interpreters. Experience in the organization and functioning of an American translators' training system is promising and useful for Ukrainian educators. US higher educational institutions offer the following translators' training program levels: Associate's degree, Bachelor's degree, Master's degree, Doctorate degree. In addition to academic training the courses and programs to obtain certificates are offered in the United States. In the system of education of America a multi-level translators' training suggests specialization, takes into account labour market trends and provides a wide choice of the path of learning of both students and already practicing translators.